THE REFINED METHOD OF SAMPLE PREPARATION AND CHEMICAL ANALYSIS FOR REFRACTORY GOLD-SILVER ORES: CASE STUDY OF THE MAISK DEPOSIT, PRIMORYE - Loseva O.V.; Radomskaya V.I.; Rogulina L.I. (My University, 2006)
The Maisk gold–silver deposit is located in the Dal’negorsk ore district of the Primor’e region. In terms of geological setting, the deposit is confined to the southeastern part of the Dal’negorsk volcanotectonic dome in the Primor’e sector of the East Sikhote-Alin volcanic belt. The Dal’negorsk ore district is composed of Upper Cretaceous acid and intermediate effusives that are superimposed on Lower Cretaceous accretionary-folded rocks of the Taukha terrane including Late Cretaceous granite, granodiorite, and gabbrodiorite plutons. The Taukha terrane incorporates Early Cretaceous continental-margin turbidites and olistostromes coupled with Triassic–Jurassic oceanic formations.
Keywords: Maisk deposit; Primorye; Mesozoic::Cretaceous; Мезозой::Меловая